Endometrial injury concurrent with hysteroscopy increases the expression of Leukaemia inhibitory factor: a preliminary study - Suat Suphan Ersahin; Aynur Ersahin (BMC, 2022)
Abstract Objective It is not known by which mechanism endometrial injury increases pregnancy rates. Leukaemia inhibitory factor (LIF) is a cytokine involved in wound healing and implantation. The aim of this study was to determine the change in endometrial LIF mRNA expression before and after mechanical injury during hysteroscopy. Methods Forty patients with a history of two or more unsuccessful implantations who decided to undergo hysteroscopy in the proliferative phase were divided into two equal groups: one with endometrial injury (scratching group) and the other with noninjury (control group). Endometrial sampling was conducted before injury on the patients in the scratching group, and then injury was performed with monopolar needle forceps. Only diagnostic hysteroscopy was performed on the patients in the control group. Endometrial tissues were collected using a Pipelle catheter between Days 20 and 23 of the mid-luteal phase of the next cycles in both the scratching and control groups. Endometrial LIF mRNA expression was evaluated with the use of reverse-transcription polymerase chain reactions. Results Relative changes in mRNA expression levels of the LIF gene in endometrial samples taken before and after injury were calculated using the 2-ΔΔCt method, and the fold changes obtained were compared between and within the groups. Compared with preinjury values, an 11.1-fold increase was found in postinjury LIF mRNA expression in patients with monopolar forceps injury (p < 0.001). There was a 3.9-fold significant increase in postinjury LIF mRNA levels compared with those in the control group (p < 0.02). Conclusions The fertility-promoting effect of hysteroscopy-guided mechanical endometrial injury may be mediated by LIF mRNA.